APP Empire: Make money, have a life and let technology work for you - Mureta, Chad, 1981- (Wiley, 2012)
"A guide to building wealth by designing, creating, and marketing a successful app across any platformChad Mureta has made millions starting and running his own successful app business, and now he explains how you can do it, too, in this non-technical, easy-to-follow guide. Make Millions with Apps provides the confidence and the tools necessary for taking the next step towards financial success and freedom. The book caters to many platforms including iPhone, iPad, Android, and BlackBerry.This book includes real-world examples to inspire those who are looking to cash in on the App gold rush. Learn how to set up your business so that it works while you don't, and turn a simple idea into a passive revenue stream. Discover marketing strategies that few developers know and/or use Learn the success formula for getting thousands of downloads a day for one App Learn the secret to why some Apps get visibility while others don't Get insights to help you understand the App store market Make Millions with Apps delivers advice on the most essential things you must do in order to achieve success with an app. Turn your simple app idea into cash flow today!"--